Factors influencing market value of agricultural land and fair compensation - Chaudhary, Dhananjay; Tiwari, Rajesh; Taneja, Sanjay; Johri, Amar; Uddin, Moin; Shamsuddin, Zelhuda (Frontiers in Sustainability, 2025)
The current research focuses on reviewing the relevant factors responsible for developing a farming community in India. A significant segment of the Indian population depends upon agriculture. For the development of the economy, there must be proper formulation and execution of relevant policies. A review of related studies was conducted to find the dominant variables responsible for developing farming communities and providing sustainable livelihood to farmers. The review brings out some significant variables, and the importance of those variables is justified by the network analysis of how the keywords are used in research. The collective approach of reviewing related studies and keyword analysis helped frame a framework for achieving sustainable livelihood amongst agriculturalists. The current study constructs valuable discernment associated with the facets that need to be concentrated on in ripening the farming sector of the Indian economy. Moreover, the current examination requires an empirical investigation of the variables accentuated in the present contemplation based on a review steered.